International Spillovers of Interest Rate Shocks: An Empirical Analysis - Rout, Sanjay Kumar; Mallick, Hrushikesh (Asian Journal of Empirical Research, 2020)
This study attempts to empirically establish a comparative agreement of cross-country spillover of real overnight, short and long-term interest rates of US, Japan, Germany, China, India, and Russia. It examines whether the magnitude of international spillovers of real interest rate shocks do vary based on their maturity pattern? Employing Diebold and Yilmaz (DY) spillover methods, this study discovered that interest rate shock spillovers vary over their different maturities. Specifically, it finds that the total spillover through long-term interest rate is 44.8%, spillover through overnight interest rate is 41.10% and spillover through short-term interest rate is 37.50%. It indicates that spillover is marginally higher via long-term interest rate compared to overnight and short-term interest rates. This is because long-term interest rate takes a secular trend path based on the preferences of international investors and conditions of the global financial market. This has a significant policy bearing for monetary and fiscal authorities, portfolio managers (including traders in stock markets), foreign and domestic investors, etc.